Mechanism of DNA flexibility enhancement by HMGB proteins - Zhang, Jingyun (Oxford University Press, 2009)
The mechanism by which sequence non-specific DNA-binding proteins enhance DNA flexibility is studied by examining complexes of double-stranded DNA with the high mobility group type B proteins HMGB2 (Box A) and HMGB1 (Box A+B) using atomic force microscopy. DNA end-to-end distances and local DNA bend angle distributions are analyzed for protein complexes deposited on a mica surface. For HMGB2 (Box A) binding we find a mean induced DNA bend angle of 78°, with a standard error of 1.3° and a SD of 23°, while HMGB1 (Box A+B) binding gives a mean bend angle of 67°, with a standard error of 1.3° and a SD of 21°. These results are consistent with analysis of the observed global persistence length changes derived from end-to-end distance measurements, and with results of DNA-stretching experiments. The moderately broad distributions of bend angles induced by both proteins are inconsistent with either a static kink model, or a purely flexible hinge model for DNA distortion by protein binding. Therefore, the mechanism by which HMGB proteins enhance the flexibility of DNA must differ from that of the Escherichia coli HU protein, which in previous studies showed a flat angle distribution consistent with a flexible hinge model.